Determinants of quality of life in Brazilian patients with myasthenia gravis - Aline Mansueto Mourão; Rodrigo Santiago Gomez; Luiz Sergio Mageste Barbosa; Denise da Silva Freitas; Elizabeth Regina Comini-Frota; Arthur Kummer; Stella Maris Aguiar Lemos; Antonio Lucio Teixeira (Clinics)
OBJECTIVES: The aims of the current study were 1) to evaluate the reliability and validity of the Brazilian version of the 15-item Myasthenia Gravis Quality of Life Scale and 2) to investigate the quality of life of Brazilian patients with myasthenia gravis and its determinants. METHODS: This cross-sectional study included 69 patients with myasthenia gravis who underwent neurological evaluation and completed questionnaires regarding quality of life (the 36-item Short Form of the Medical Outcomes Study and the 15-item Myasthenia Gravis Quality of Life Scale), anxiety and depressive symptoms. RESULTS: The Brazilian version of the 15-item Myasthenia Gravis Quality of Life Scale showed high internal consistency and good concurrent validity with the 36-item Short Form of the Medical Outcomes Study and its subscales. Determinants of quality of life in Brazilian patients with myasthenia gravis included the current status of myasthenia gravis as assessed by the Myasthenia Gravis Composite, the current prednisone dose and the levels of anxiety and depression. CONCLUSION: The Brazilian version of the 15-item Myasthenia Gravis Quality of Life Scale is a valid instrument. Symptom severity, prednisone dosage and anxiety and depression levels impact the quality of life of patients with myasthenia gravis.